A planetary‐scale disturbance in the most intense Jovian atmospheric jet from JunoCam and ground‐based observations. Issue 10 (25th May 2017) - Sánchez‐Lavega, A.; Rogers, J. H.; Orton, G. S.; García‐Melendo, E.; Legarreta, J.; Colas, F.; Dauvergne, J. L.; Hueso, R.; Rojas, J. F.; Pérez‐Hoyos, S.; Mendikoa, I.; Iñurrigarro, P.; et al.
Abstract: We describe a huge planetary‐scale disturbance in the highest‐speed Jovian jet at latitude 23.5°N that was first observed in October 2016 during the Juno perijove‐2 approach. An extraordinary outburst of four plumes was involved in the disturbance development. They were located in the range of planetographic latitudes from 22.2° to 23.0°N and moved faster than the jet peak with eastward velocities in the range 155 to 175 m s −1 . In the wake of the plumes, a turbulent pattern of bright and dark spots (wave number 20–25) formed and progressed during October and November on both sides of the jet, moving with speeds in the range 100–125 m s −1 and leading to a new reddish and homogeneous belt when activity ceased in late November. Nonlinear numerical models reproduce the disturbance cloud patterns as a result of the interaction between local sources (the plumes) and the zonal eastward jet. Key Points: A planetary‐scale disturbance developed in the highest‐speed Jupiter jet at 23.5°N latitude during October and November 2016 Four "plumes" were involved in the outbreak moving with speeds between 155 and 175 m s −1, the fastest features at cloud level Nonlinear numerical models reproduce the disturbance from the interaction between local sources (the plumes) and the zonal eastward jet